How do Head-mounted Displays and Planning Strategy Influence Problem-solving-based Learning in Introductory Electrical Circuit Design? - Bian Wu; Yiling Hu; Minhong Wang (Educational Technology & Society, 2020)
The high-fidelity and interactivity afforded by head-mounted displays (HMD) has a potential to improve learning in problem-solving contexts. However, there is a lack of studies with mixed findings on the efficacy of HMD in the development of problem-solving competence. Moreover, the integration of learning strategies with HMD supported learning is often overlooked. This study aimed to address the gap by investigating whether the simulation media (HMD or 2D simulation environments) and learning strategy (with or without planning) may influence student learning with problem-solving tasks. The results show that the HMD and planning groups outperformed other groups in simulated problem-solving tasks, and in transferring the competence to real-world tasks. Students using the HMD perceived a higher level of sense of presence, self-efficacy, and simulator acceptance; but they reported a higher level of mental workload and simulator sickness than those using the 2D simulation. Implications of the findings are also discussed.